Effects of carbon and nitrogen content on seed germination of calabrian pine (Pinus brutia) populations - Caliskan, Servet; Makineci, Ender (Bosque (Valdivia), 2017)
Calabrian pine (Pinus brutia) seeds collected from fifteen populations were analyzed for their carbon (C) and nitrogen (N) content. Moreover, germination percentages (GP) and mean germination times (MGT) of the seeds were evaluated based on their carbon and nitrogen concentrations, C/N ratio, total carbon mass (CM), and total nitrogen mass (NM). Except for C/N ratios, variables showed significant differences among populations. The highest seed carbon concentration was 54 %, and the lowest was 50 %. Seed nitrogen concentrations varied from 2.6 % to 3.2 %. The highest correlations were found between the GP of chilled filled seeds (GPFS) and the combined concentrations of carbon and nitrogen (R2 = 0.65) and the GPFS and concentrations of carbon (R2 = 0.63), both being significant. The relationships between germination parameters and combined concentrations of carbon and nitrogen as well as CM and NM traits were generally higher than any found in individual evaluations, except for the concentrations of carbon.